Geriatric patient in the practice of emergency medical teams – observation in 2020–2022 - Czyżewski, Łukasz; Dudziński, Łukasz; Wyzgał, Janusz (Frontiers in Medicine, 2023)
Analysis of interventions of medical rescue teams for geriatric patients in a three-year period, taking into account the causes, circumstances, medical management, pharmacology.The study included a 3-year retrospective analysis of the trips of medical rescue teams in the northern part of the Lubelskie Voivodeship in the period from January 1, 2020 to December 31, 2022. The data comes from medical documentation. Interventions caused by a health risk in a patient in the 90+ age group were qualified as events. 897 EMT interventions were qualified (2020-327, 2021-269, 2022-301) constituting 4.29% of all interventions carried out in the operational area. In addition, a quantitative analysis of a comparative group of patients aged 80-89 was performed.It was shown that the time of rescue activities was the longest for injuries and the shortest for mental disorders (60 ± 31 vs 43 ± 21 min). It was shown that specialist EMT teams (S) were statistically significantly more often called for cardiology disorders (63%). It was shown that pharmacological agents were used statistically significantly more often in respiratory disorders (83%) compared to neurology disorders (47%), P < 0.001. It was also shown that patients whose call was caused by neurology disorders were statistically more often transported to the emergency department (N= 76, 76%), P<0.001The causes of calls regarding disorders of the circulatory and respiratory systems most often require the implementation of pharmacology during EMT interventions, mainly shortterm and symptomatic drugs. Interventions to rural areas dominate in the presented analysis in each year of the analysis and in each group of reasons for calls, which may be associated with more difficult access to a primary care physician. Most EMT interventions concern exacerbation of chronic diseases. Transport to the hospital was necessary mainly due to neurological and traumatic calls